2020
DOI: 10.1371/journal.pone.0225487
|View full text |Cite|
|
Sign up to set email alerts
|

G82S RAGE polymorphism influences amyloid-RAGE interactions relevant in Alzheimer’s disease pathology

Abstract: Receptor for advanced glycation end products (RAGE) has been implicated in the pathophysiology of Alzheimers disease(AD) due to its ability to bind amyloid-beta (Aβ42) and mediate inflammatory response. G82S RAGE polymorphism is associated with AD but the molecular mechanism for this association is not understood. Our previous in silico study indicated a higher binding affinity for mutated G82S RAGE, which could be caused due to changes in N linked glycosylation at residue N81. To confir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…RAGE blockade leads to reduced microglial migration toward Aβ deposits (Lue et al, 2001 ). More recently, numerous studies have reported the pathogenic role of RAGE in AD progression, which promotes the release of pro-inflammatory mediators by activated microglia (Fang et al, 2010 ; Deane et al, 2012 ; Cathrine C et al, 2020 ). A potent multimodal RAGE blocker effectively inhibited the microglial activation and neuroinflammatory response to Aβ and improved the cognitive performance in AD transgenic mice (Deane et al, 2012 ).…”
Section: Microglia and Admentioning
confidence: 99%
“…RAGE blockade leads to reduced microglial migration toward Aβ deposits (Lue et al, 2001 ). More recently, numerous studies have reported the pathogenic role of RAGE in AD progression, which promotes the release of pro-inflammatory mediators by activated microglia (Fang et al, 2010 ; Deane et al, 2012 ; Cathrine C et al, 2020 ). A potent multimodal RAGE blocker effectively inhibited the microglial activation and neuroinflammatory response to Aβ and improved the cognitive performance in AD transgenic mice (Deane et al, 2012 ).…”
Section: Microglia and Admentioning
confidence: 99%
“…The non-synonymous replacement of glycine by serine at the 82nd position of RAGE caused by rs2070600 induces changes in the structure of the variable domain of RAGE, which can potentially affect AGE–RAGE signaling. In vitro studies have elucidated that RAGE with rs2070600 has a higher binding affinity for amyloid-beta peptides (Aβ42) and prototypic S100/cangrulin, which upregulated inflammatory mediators. , Substitution of glycine with serine at the 82nd position of RAGE promotes N-linked glycosylation of adjacent asparagine residue at the 81st position, which may also affect ligand binding and further downstream signaling initiated by AGE–RAGE interaction . Several studies have also found a significantly lower plasma sRAGE level in the subjects carrying rs2070600, ,,, and the same has been elucidated using a cell culture model .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, human RAGE is encoded by the AGER gene, which presents multiple single-nucleotide polymorphisms. Different studies have reported a direct link between AGER genetic polymorphisms and the severity of different pathological conditions, including non-alcoholic fatty liver disease, 68 cancer, 69 Alzheimer’s disease, 70 and cardiovascular disorders. 71 A direct contribution of these comorbidities to the RAGE expression levels cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%